New research tools suggest a “levels-less” image of the behaving organism and dissolution of the reduction vs. anti-reduction dispute - Bickle, John; De Sousa, André F.; Silva, Alcino J. (Frontiers in Psychology, 2022)
A kind of “ruthless reductionism” characterized the experimental practices of the first two decades of molecular and cellular cognition (MCC). More recently, new research tools have expanded experimental practices in this field, enabling researchers to image and manipulate individual molecular mechanisms in behaving organisms with an unprecedented temporal, sub-cellular, cellular and even circuit-wide specificity. These tools dramatically expand the range and reach of experiments in MCC, and in doing so they may help us transcend the worn-out and counterproductive debates about “reductionism” and “emergence” that divide neuroscientists and philosophers alike. We describe examples of these new tools and illustrate their practical power by presenting an exemplary recent case of MCC research using them. From these tools and results we provide an initial sketch of a new image of the behaving organism in its full causal-interactive complexity, with its molecules, cells and circuits combined within the single system that it is. This new image stands in opposition to the traditional “levels” image of the behaving organism, and even the initial sketch we provide of it here offers hope for avoiding the dreary metaphysical debates about “emergence” and “downward causation,” and even the reduction versus anti-reduction dispute, all dependent upon the familiar “levels” image.